Open-Label Study of the Safety and Pharmacokinetics of Solifenacin in Subjects With Hepatic Impairment - Mirjam Kuipers; Ronald Smulders; Walter Krauwinkel; Timothy Hoon (Elsevier, 2006)
Determining the pharmacokinetics and safety of solifenacin succinate, a once-daily, oral antimuscarinic agent indicated for treatment of overactive bladder, in subjects with hepatic impairment. In this open-label study, 16 subjects (eight with moderate hepatic impairment [defined as a Child-Pugh score of 7 - 9], eight healthy) received a single oral 10 mg solifenacin dose. Blood and urine were collected for pharmacokinetic assessments. Pharmacokinetic parameters (primary: area under the plasma concentration-time curve from time 0 to infinity [AUC0-∞] and maximum plasma concentration [Cmax]) and safety were evaluated for solifenacin and its metabolites. There were no clinically relevant differences in safety. Moderate hepatic impairment increased AUC0-∞ by 60%, and the mean elimination half-life of solifenacin and several of its metabolites was longer versus healthy subjects. Mean Cmax values were comparable between the groups. A single oral dose of solifenacin was well tolerated in hepatically impaired and healthy subjects; however, moderate hepatic impairment influenced solifenacin pharmacokinetics. In patients with mild hepatic impairment, solifenacin may be used without special caution; however, in patients with moderate hepatic impairment, doses greater than 5 mg are not recommended and the 5 mg dose should be used with caution. Keywords:: hepatic impairment, overactive bladder, pharmacokinetics, safety and tolerability, solifenacin